Nitrogen Fixation 2020
DOI: 10.5772/intechopen.90699
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Nitrogen Fertilization on Tropical Environmental

Abstract: The nitrogen (N) fertilization synthetic or biological is primordial for food production worldwide. The consumption of N fertilizers in agricultural systems increased in exponential scale, mainly in developing countries. However, some negative points are associated to industrial N consumption; consequently the industry promoted ways to minimize N losses in production systems of tropical agriculture. Biological nitrogen fixation is a very important natural and sustainable process for the growth of leguminous pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In the literature, there are reports of both increased and decreased accumulation of L-Pro following treatment with Si under salt or drought stress (Zhu et al, 2020;Basilio-Apolinar et al, 2021). Research on okra (Abelmoschus esculentus), Glycyrrhiza uralensis, P. vulgaris, and Capsicum annuum found that Si protected the plants against saline stress by inducing higher content of free L-Pro (Soares Pereira et al, 2013;Abbas et al, 2015;Rady et al, 2019;Cui et al, 2021), but the decreased level of L-Pro induced by Si was reported for wheat and soybean (Lee et al, 2010;Bybordi, 2015;Singh et al, 2022). In a recent study, the modulation of L-Pro by Si in cucumber seedlings was found to be time-dependent, i.e., L-Pro increased compared to control during the first days after NaCl + Si treatment, and started to decrease 6 days after the treatment (Zhu et al, 2020).…”
Section: The Effects Of Alginate-sinp Biostimulant On the Antioxidant...mentioning
confidence: 99%
“…In the literature, there are reports of both increased and decreased accumulation of L-Pro following treatment with Si under salt or drought stress (Zhu et al, 2020;Basilio-Apolinar et al, 2021). Research on okra (Abelmoschus esculentus), Glycyrrhiza uralensis, P. vulgaris, and Capsicum annuum found that Si protected the plants against saline stress by inducing higher content of free L-Pro (Soares Pereira et al, 2013;Abbas et al, 2015;Rady et al, 2019;Cui et al, 2021), but the decreased level of L-Pro induced by Si was reported for wheat and soybean (Lee et al, 2010;Bybordi, 2015;Singh et al, 2022). In a recent study, the modulation of L-Pro by Si in cucumber seedlings was found to be time-dependent, i.e., L-Pro increased compared to control during the first days after NaCl + Si treatment, and started to decrease 6 days after the treatment (Zhu et al, 2020).…”
Section: The Effects Of Alginate-sinp Biostimulant On the Antioxidant...mentioning
confidence: 99%